Equality as a Constitutional Value: The Principle of Equality in EU Law - Staničić, Frane (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
The principle of equality should be considered as a fundamental legal principle in any system of law. It can be considered as a principle governing people’s rights (everyone is equal before the law) and/or as a principle governing equality among states. This study explores the latter. First, it provides a theoretical definition of the principle of equality as considered by legal theorists. Thereafter, it discusses its implementation in international organisations and its possible limitations considering the membership in an international organisation. In the next part this principle will be analysed as a central principle of EU law, particularly its development in its use between EU Member States and the differentiation mechanisms used in the European Union’s integration process. The aim of this study cannot be achieved without considering the insights from the case law of the CJEU, therefore, its overview will be provided in the next part. Special focus will be placed on the identity clause enshrined in Art. 4(2) of the TEU as this is crucial in the context of the correct implementation of the principle of equality of Member States. A special focus will be placed on the meaning of the identity clause in the context of the principle of supremacy of EU law as the absolute interpretation if this principle in the case law of the CJEU threatens to endanger the principle of equality with regard to Member States.